Oral supplementation of Njansan (Ricinodendron heudelotii Bail) and sardine fillets (Sardina pilchardus) oils alleviate high-fat diet-induced obesity in rats by regulating lipid metabolism and stress oxidative parameters - Soh Nde Florent; Ghomdim Nzali Horliane; Ejoh Aba Richard; Tchiegang Clergé (Asian Journal of Medical Sciences, 2024)
Background: Obesity has become one of the most common metabolic disorders in the world, characterized by the accumulation of excess fat in the body. Research into natural compounds to improve obesity has become increasingly important.